The Influence of Parents' Influence on the Development of Religious and Oral Religions of Children 5-6 Years in Sentang Village, Asahan Regency - Vivi Chairunisa; Yus, Anita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of people's parenting style on the development of religious and moral values of children aged 5-6 years in Sentang Village. This type of research is conducted using a comparative causal design. The population in the study was 305 parents and 305 children, then the sample of this study used a non-probability sampling technique, which is a technique that does not provide the same opportunity to each sample member. The sample of this study is 30 children aged 5-6 years in Sentang Village. The data was obtained by observation techniques using questionnaire instrument sheets and observation sheets. Technique Data analysis uses parametric statistics with simple linear regression. The results of the test showed that parenting style had a significant influence on the development of children's religious values and morals. The results of the simple linear regression hypothesis test of 1,721 > 1,706 (authoritarian), 2,884 > 1,706 (democratic), -2,025 < 1706 (permissive) proved that Ha was accepted and Ho was rejected. Thus, it can be concluded that there is a significant influence on the parenting style of people (authoritarian, democratic, and permissive) on the development of religious and moral values of children aged 5-6 years in Sentang Village, Asahan Regency. Based on the results, the study suggests that parents can apply democratic parenting to improve the development of religious values and morals of children aged 5-6 years.